THE IMPLEMENTATION OF ARABIC LANGUAGE LEARNING AT THE UMMATUL MUKMININ GIRLS' ISLAMIC BOARDING SCHOOL, MEDAN - Regina Valda Garzita; Rahmaini Rahmaini (Ihya al-Arabiyah: Jurnal Pendidikan Bahasa dan Sastra Arab, 2025)
This study examines the implementation of contextual teaching strategies in Arabic language learning at the Ummatul Mukminin Girls' Islamic Boarding School in Medan. The research was conducted using a qualitative descriptive approach through observations, in-depth interviews, and documentation. Findings show that the contextual teaching strategy was applied gradually yet increasingly consistently, integrating key components such as inquiry, modeling, reflection, and authentic assessment. The strategy successfully encouraged students to engage more actively in daily Arabic communication and improved their confidence in speaking. Supporting factors included the school's religious environment and teachers' creativity, while constraints involved students' initial reliance on memorization-based methods and limited modern learning facilities. Overall, the contextual teaching strategy proved effective in transforming learning from rote memorization into meaningful, experience-based language use.